Nurses Experience and Perceived Challenges of Using Nonpharmacological Pain Interventions for Musculoskeletal Pain: A Qualitative Study - Israa A. M. Abuijlan RN, MSN; Priyalatha Muthu RN, MSN, PhD; Manju Nair Avinash RN, MSN, PhD (SAGE Publishing, 2023)
Introduction Current musculoskeletal pain management guidelines encourage utilizing nonpharmacological pain measures. Despite their positive effect in alleviating musculoskeletal pain, nurses reported negative attitudes toward utilizing nonpharmacological pain measures. Therefore, assessing nurses' perception of nonpharmacological pain measures is essential to promote patient comfort. Objective The aim of the study was to explore the nurses' experience and perceived challenges in using nonpharmacological pain measures in caring for patients with musculoskeletal pain. Materials & Methods A descriptive qualitative design was carried out. Face-to-face semistructured interviews were conducted among 11 nurses. Colaizzi's method was employed in analyzing the data. Results Four themes emerged, namely, constant monitoring and observation, selection of nonpharmacological pain measures, and various barriers related to patients and nurses. One of the ways to overcome these barriers or challenges, we should promote interprofessional teams in planning patient-centered pain management care. Also, defining the role of the pain management nurse would be pivotal to ensuring effective pain management measures. Conclusion The nursing workforce needs to initiate and utilize these measures as a common practice in managing musculoskeletal pain and in turn create a culture that strongly supports the utilization of nonpharmacological pain measures.